Expression of the inhibitor of apoptosis protein family in multiple sclerosis reveals a potential immunomodulatory role during autoimmune mediated demyelination - Hebb, ALO; Moore, CS; Bhan, V; Campbell, T; Fisk, JD; Robertson, HA; Thorne, M; Lacasse, E; Holcik, M; Gillard, J; Crocker, SJ; Robertson, GS (Multiple sclerosis, 2008)
A failure of autoreactive T cells to undergo apoptosis may contribute to the pathogenesis of multiple sclerosis (MS). The role of the inhibitor of apoptosis (IAP) family of anti-apoptotic proteins such as X-linked IAP (XIAP), human inhibitor of apoptosis-1 (HIAP-1), human inhibitor of apoptosis-2 (HIAP-2), neuronal apoptosis inhibitory protein (NAIP) and Survivin in relapsing–remitting, secondary-progressive, primary-progressive or benign forms of MS is unclear. We report here that expression of the IAP family of genes in peripheral blood samples and brain tissues from MS cases support a role for differential regulation of these potent anti-apoptotic proteins in the pathology of MS. XIAP mRNA and protein levels were elevated in peripheral blood mononuclear cells from patients with active disease relative to normal subjects. In patients with active MS, HIAP-1 and HIAP-2 mRNA levels were elevated in resting T cells while NAIP mRNA was increased in whole blood. In post-mortem MS brain tissue, XIAP and HIAP-1 in myelin lesions were co-localized with microglia and T cells, respectively. Only in primary-progressive patients was Survivin expression elevated suggestive of a distinct pathological basis for this subtype of MS. Taken together, these results suggest that patterns of inhibitor of apoptosis expression in immune cells may have value in distinguishing between MS subtypes and offer insight into the mechanisms responsible for their distinct clinical courses.